SISTEM KUNCI DAN ALARM OTOMATIS PADA PAGAR RUMAH MENGGUNAKAN FINGERPRINT BERBASIS ARDUINO UNO - Dennis, Nigel; Nopriadi, Nopriadi (Computer Science and Industrial Engineering, 2023)
Technology in this era is growing rapidly and cannot be separated in many significant influences. In this era many systems are very fast and efficient in a good and the best way including security system such as automatic lock security. The security system which are very much found in the community and one of the security system is security for house fence. In this system there is so many and dangerous problems that cause robbery and the fence being destroy by bad people starting from several case and a lot of criminals that been found because the lock security system is not in a good way. There is a lot of fence and house are not in a good and automatic security dan make everyone is safe and lock the house especially the fence without feeling worried.In this research the authors conducted some major impact based on the background that has been explain by creating an automatic lock system for fences using arduino technology which is the center and the core of this research and this research is using fingerprint as a tool to be able to open an automatic lock system and it can open.